Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1016/j.ydbio.2003.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Formation, architecture and polarity of female germline cyst in Xenopus

Abstract: Little is known about the formation of germline cyst and the differentiation of oocyte within the cyst in vertebrates. In the majority of invertebrates in the initial stages of gametogenesis, male and female germ cells develop in full synchrony as a syncytia of interconnected cells called germline cysts (clusters, nests). Using electron microscopy, immunostaining and three-dimensional reconstruction, we were able to elucidate the process of cyst formation in the developing ovary of the vertebrate Xenopus laevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
164
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 164 publications
(175 citation statements)
references
References 64 publications
4
164
0
6
Order By: Relevance
“…However, the observed pattern of microtubules does not permit full-length guidance, and oxygen gradients may play the major role in this context. For another example, a structure resembling the Drosophila fusome which is involved in anchoring centrioles and organizing the primary mitochondrial cloud around the centriole was found during female germline cyst development in Xenopus laevis (Kloc et al, 2004). Mitochondria also appear to be moved by microtubules during merozoite assembly in Plasmodium falciparum (Hopkins et al, 1999), and mitochondrial dysfunction results from abnormal microtubules in cytoplasmic male sterility of higher plants (Li et al, 2014, in conjunction with findings of Zhang et al, 2009).…”
Section: Ciliogenesis In Photoreceptor Cellsmentioning
confidence: 90%
“…However, the observed pattern of microtubules does not permit full-length guidance, and oxygen gradients may play the major role in this context. For another example, a structure resembling the Drosophila fusome which is involved in anchoring centrioles and organizing the primary mitochondrial cloud around the centriole was found during female germline cyst development in Xenopus laevis (Kloc et al, 2004). Mitochondria also appear to be moved by microtubules during merozoite assembly in Plasmodium falciparum (Hopkins et al, 1999), and mitochondrial dysfunction results from abnormal microtubules in cytoplasmic male sterility of higher plants (Li et al, 2014, in conjunction with findings of Zhang et al, 2009).…”
Section: Ciliogenesis In Photoreceptor Cellsmentioning
confidence: 90%
“…Nobox deficiency in mice and perturbation of NOBOX homeodomain in women result in the premature ovarian failure (POF) syndrome characterized by postnatal oocyte loss and the replacement of follicles by fibrous tissue [1,2,6,8,10]. In mice, as in the majority of other animal species, mitotic divisions of primary oogonia, followed by incomplete cytokinesis, lead to the formation of germ cell cysts (nests, clusters) containing several oocytes connected by intercellular bridges [11][12][13]. Subsequently, the germ cell cysts break apart: somatic cells invade the cysts and separate and surround individual oocytes, resulting in the formation of individual ovarian follicles, which, in mammals, are called primordial follicles [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In mice, as in the majority of other animal species, mitotic divisions of primary oogonia, followed by incomplete cytokinesis, lead to the formation of germ cell cysts (nests, clusters) containing several oocytes connected by intercellular bridges [11][12][13]. Subsequently, the germ cell cysts break apart: somatic cells invade the cysts and separate and surround individual oocytes, resulting in the formation of individual ovarian follicles, which, in mammals, are called primordial follicles [11][12][13]. Histological studies of oocyte development in mice between the newborn stage and day 14 after birth showed that ovaries of Nobox +/− and Nobox −/− newborns have similar overall numbers of germ cell cysts and oocytes, indicating no overall germ cell loss [7].…”
Section: Introductionmentioning
confidence: 99%
“…In both Xenopus and Drosophila, the Balbiani body arises within interconnected germline cysts by the controlled assembly of organelles and germinal granule components at the time of follicle formation (26,36). Female mouse germ cells also generate cysts after reaching the genital ridge (37).…”
mentioning
confidence: 99%